PENGARUH GOOD CORPORATE GOVERNANCE, ENVIRONMENTAL PERFORMANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP FINANCIAL PERFORMANCE (Studi Empiris pada Seluruh Perusahaan Terdaftar di BEI Mengikuti PROPER Periode Tahun 2014-2015) - Risky Vera Yoanna; Kirmizi Ritonga; Al Azhar A (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research has purposed to see the influenced of good corporate governance, environmental performance and corporate social responsibility in facing financial performance in Company Listed On Indonesia Stock Exchange Year 2014-2015. This research has two variables. They are independent and dependent variable. Dependent variable consist of financial performance of the company. Independent variabel consist comissaris independent,board of direction, audit committee, environmental performance, and corporate social responsibility. The populations of this research consist of 68 company and 74 samples company from 2014-2015 which listed in Indonesia Stock Exchange. Technique or getting sample of this research was purposive sampling. Multiple regression is used to test the hypothesis. After it was tested by using SPSS version 20.00. The result show that board of direction and environmental performance has significant impact on the financial performance. While comissaris independent, comitee audit and corporate social responsibility has no significant effect on the financial performance. Adjusted R Square shows the value of 0,125. It means that 12,5% change in financial performance is affected by the determinant variables in the model while the rest 87,5% is explained by other variables not included in the model.Keywords : Good Corporate Governance, Environmental Performance, Corporate Social Responsibility dan Financial Performance.